Planning process drama : enriching teaching and learning - Bowell, Pamela; Heap, Brian S. (Milton Park, Abingdon, Oxon ; New York : Routledge, 2013)
Process drama is now firmly established, internationally, as a powerful and dynamic pedagogy. This clear and accessible book provides a practical, step-by-step guide to the planning of process drama. Grounded in theory and illustrated in practice, it identifies and explains the principles of planning and shows how they can be applied across age ranges and curricula. Drawing on the authors' wide-ranging practical experience and research, examples are built up and run throughout the book, at each step showing how and why the teachers' planning decisions were made. This second edition features: two completely new chapters: one deals with planning for diverse learner groups and the other moves the reader on from the pre-action planning phase to the 'planning on your feet' required as the drama unfolds, a wider range of examples illustrating the planning principles in practice, incorporated new material to reflect recent understanding of how learning takes place, Written as a conversation between reader and authors, Planning Process Drama will help practitioners to update and refine their practice and strengthen their understanding, skills and confidence. Planning Process Drama will be an essential guide for students undertaking initial teacher training at Primary Level, in addition to both Drama and English at Secondary Level, and a Masters in Drama in Education. It will also prove to be valuable reading for specialist and non-specialist teacher in both the primary and secondary sectors who teach, or wish to teach, process drama. Book jacket.
Includes bibliographical references (pages 156-161) and index.
Keywords: Drama in education; Improvisation (Acting)